2021
DOI: 10.1172/jci.insight.141341
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress associated with cardiopulmonary bypass induces expression of inflammatory cytokines and necroptosis in monocytes

Abstract: Cardiopulmonary bypass (CPB) is required during most cardiac surgeries. CBP drives systemic inflammation and multi-organ dysfunction that is especially severe in neonatal patients. Limited understanding of molecular mechanisms underlying CPB-associated inflammation presents a significant barrier to improve clinical outcomes. To better understand these clinical issues, we performed the first mRNA-sequencing on total circulating leukocytes from neonatal patients undergoing CPB. Our data identified myeloid cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 30 publications
3
39
0
3
Order By: Relevance
“…We also eliminated all mRNAs that were not present in our ancillary mRNA analysis. 4 This filtering ensured that only the highest quality relationships were validated.…”
Section: Identification Of Putative Mirna Targetsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also eliminated all mRNAs that were not present in our ancillary mRNA analysis. 4 This filtering ensured that only the highest quality relationships were validated.…”
Section: Identification Of Putative Mirna Targetsmentioning
confidence: 99%
“…In a previous study using a separate population, we identified 2, 688 genes which exhibited temporal dysregulation after CPB, which were categorized into 5 distinct groups. 4 We expanded on this analysis to investigate relationships between these differentially expressed genes (DEGs) and the miRNA target genes identified in this analysis. 1,046 of these 2,688 DEGs (38.9%) were reported targets of differentially expressed miRNAs, as shown in Table 2 and Figure 1C.…”
Section: Identification Of Differentially Expressed Mirnas In Different Stages Of Cpbmentioning
confidence: 99%
See 2 more Smart Citations
“…In most surgeries, where heavy bleeding is expected, such as hip replacement, openheart, or aorta surgeries, blood is aspirated using a vacuum blood sucker and retransfusion of the aspirated blood is routinely performed to avoid allogeneic blood transfusions [4]. The coagulation, fibrinolysis, and inflammation in the sucked blood are strongly activated [5,6]. Furthermore, cells are exposed to shear stress, which can lead to their destruction [7].…”
Section: Introductionmentioning
confidence: 99%